STUDIES IN THE THIOPHENE SERIES II PREPARATION AND PHYTOCHEMICAL REDUCTION OF2 2 THENOINAND2 2 THENIL - NORD, FF; KINGW, J; DESCHAMPS, IGNACIO (FORDHAM UNIVERSITY, DEPARTMENT OF ORGANIC CHEMISTRY, NEW YORK, NY, EUA, 1951)
1. A method is presented for the preparation of 2,2â ²-thenoin and 2,2â ²-thenil. 2. Phytochemical reduction was shown to be applicable to both compounds. 3. Differences in the phytochemical reducibility of these compounds in contrast to benzoin and furil
J REPROD FERTIL
Keywords: STUDIES, THIOPHENE SERIES, PREPARATION, PHYTOCHEMICAL REDUCTION, 2 2 THENOINAND2 2 THENIL; QUIMICA; QUIMICA ORGANICA; MECANISMOS DE REACCION